ACTUAL QUESTIONS THE FIGHT AGAINST ECONOMIC CRIME IN THE MODERN RUSSIAN SOCIETY - Dmitry V. Dianov; Andrey N. Ishchenko (Статистика и экономика)
The article is devoted to the economic phenomenon that originated «under the curtain» of the socialist system, when high-ranking government figures, formed the first organized clans on the basis of family and downto-earth and friendly relations, which turned into a corrupt group and evolved later into a complete system of economic crime in modern Russia. This paper presents a qualitative analysis of categorical apparatus that allows you to specify the relationship and complementarity of organized and economic crime.